Co-operative effect of MCF and MAF(IFN-gamma) in the protection of mice against Listeria monocytogenes. - Handa, T (1988)
The effects of macrophage chemotactic factor (MCF) and macrophage-activating factor (MAF) on protection to Listeria monocytogenes were analysed using 'MCF-rich fraction' and murine recombinant interferon-gamma (rIFN-gamma). Recombinant IFN-gamma showed no macrophage chemotactic activity in the assays performed in vitro and in vivo. Although a single injection of either MCF-rich fraction or rIFN-gamma into the footpads of mice led to a significant degree of anti-listerial activity, the highest degree of protection was observed when injected together. The i.v. administration of 20,000 U rIFN-gamma did not raise significant protective activity against Listeria; however, injection with rIFN-gamma prior to that with the MCF-rich fraction into the footpad produced a higher level of protective activity than the group treated with MCF alone. In addition to MAF(IFN-gamma), MCF seems to play another important role in the full expression of protection against L. monocytogenes.